2018
DOI: 10.18632/oncotarget.26298
|View full text |Cite
|
Sign up to set email alerts
|

EpCAMhigh and EpCAMlow circulating tumor cells in metastatic prostate and breast cancer patients

Abstract: The presence of high expressing epithelial cell adhesion molecule (EpCAMhigh) circulating tumor cells (CTC) enumerated by CellSearch® in blood of cancer patients is strongly associated with poor prognosis. This raises the question about the presence and relation with clinical outcome of low EpCAM expressing CTC (EpCAMlow CTC). In the EU-FP7 CTC-Trap program, we investigated the presence of EpCAMhigh and EpCAMlow CTC using CellSearch, followed by microfiltration of the EpCAMhigh CTC depleted blood. Blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 26 publications
6
76
0
Order By: Relevance
“…This approach was shown to result in a loss of a substantial percentage of EpCAMl ow CTCs, but these cells were shown to have no impact on overall survival (OS) in metastatic breast cancer. Conversely, the presence of EpCAM high cells was demonstrated to be strongly related to poor survival [40]. Examples of EpCAM heterogeneous expression among CTCs from patients with MBC are presented in Figure 2.…”
Section: Changes In Expression; Reversible Re-programingmentioning
confidence: 99%
“…This approach was shown to result in a loss of a substantial percentage of EpCAMl ow CTCs, but these cells were shown to have no impact on overall survival (OS) in metastatic breast cancer. Conversely, the presence of EpCAM high cells was demonstrated to be strongly related to poor survival [40]. Examples of EpCAM heterogeneous expression among CTCs from patients with MBC are presented in Figure 2.…”
Section: Changes In Expression; Reversible Re-programingmentioning
confidence: 99%
“…Observation in NSCLC, breast and prostate cancer showed that frequently both EpCAM + and EpCAM − CTC populations are present and rarely only one of the two are detected. Moreover, in patients with metastatic NSCLC and prostate cancer we found that the EpCAM + , CK + CTC, and not the EpCAM − , CK + are correlated with poor outcome (46)(47)(48). Hopefully research will be conducted with the newly available technology that can provide in depth information on the frequency of different subpopulations of CTC, other (rare) cell types and their relation with the disease.…”
mentioning
confidence: 99%
“…The fluorescent images were obtained from 7.5 mL blood samples from metastatic prostate and non-small cell lung cancer patients (13)(14)(15). The fluorescent images were obtained from 7.5 mL blood samples from metastatic prostate and non-small cell lung cancer patients (13)(14)(15).…”
Section: Selection Of Fluorescent Cell Images For Ctc Scoringmentioning
confidence: 99%
“…A set of 100 fluorescent cell images comprising of potential CTCs and leukocytes was assembled. The fluorescent images were obtained from 7.5 mL blood samples from metastatic prostate and non-small cell lung cancer patients (13)(14)(15). The blood was processed with the CellSearch system (Menarini Silicon Biosystems, Huntingdon Valley, PA, USA) and the EpCAM depleted blood was collected, passed through microsieves (VyCap, Deventer, The Netherlands), fluorescently labeled and images taken by fluorescent microscopy (13).…”
Section: Selection Of Fluorescent Cell Images For Ctc Scoringmentioning
confidence: 99%
See 1 more Smart Citation